Impact of Cash Management Practices and Financial Performance of Small-Scale Businesses: A Case Study of Small-Scale Businesses in Mukono Central Division - Clare Atuhaire (Uganda Christian University, 2024)
This study investigated the impact of cash management practices on the financial performance of small scale businesses in Mukono Central Division, focusing on the importance of maintaining business records, preparing cash budgets, and managing accounts receivable. A cross-sectional research design was employed, to explore the relationship between working capital management and financial performance. The study targeted a population of 100 registered small-scale enterprises, with a sample size of 75 respondents selected through Krejcie and Morgan's sample size table. Data was collected using questionnaires and analyzed using SPSS software. The findings reveal a strong consensus among respondents regarding the benefits of meticulous record keeping for financial planning, tax compliance, and decision-making. However, there are areas where improvements in understanding and implementation could enhance credit evaluation and regulatory adherence. Similarly, there is significant agreement among small-scale business owners on the efficacy of cash budgets in bolstering financial performance, particularly in managing cash flows and mitigating risks. Nonetheless, varying levels of understanding and utilization indicate room for improvement in utilizing cash budgets for financial health assessment and revenue growth. Furthermore, the study highlights the critical role of efficient accounts receivable management in improving cash flow, maintaining liquidity, and minimizing the need for external financing. Timely collection of payments emerges as crucial for optimizing working capital, enhancing profitability, and mitigating default risks. The emphasis on accurate data underscores the importance of robust accounting practices for informed decision-making. Based on the findings, recommendations include leveraging internet-based innovations for cash management, utilizing computerized accounting packages for financial reporting, and availing training programs to enhance financial management skills among SME owners/managers. These interventions can contribute to improving financial performance and operational sustainability within the small-scale business sector.